N‑Cadherin Nanoantagonist Driven Mesenchymal-to-Epithelial Transition in Fibroblasts for Improving Reprogramming Efficiency - Meng, Xia; Zhou, Anwei; Huang, Yu; Zhang, Yu; Xu, Yurui; Shao, Kaifeng; Ning, Xinghai (Nano letters, 2021)
Induced pluripotent stem cells (iPSCs) hold promise in revolutionizing medicine; however, their application potential is limited because of low reprogramming efficiency. Mesenchymal-to-epithelial transition (MET) has been proved to involve reprogramming of somatic cells into iPSCs, making it a promising target for enhancing generation of iPSCs. Here, we nanoengineered N-cadherin-blocking peptide ADH-1 with gold nanoparticles, generating a multivalent N-cadherin antagonist (ADH-AuNPs), for improving reprogramming efficiency through driving cell MET. ADH-AuNPs exhibited good biocompatibility and showed higher N-cadherin inhibitory activity than ADH-1 due to multivalency, thereby enhancing cell-state reprogramming toward epithelial lineages. Particularly, ADH-AuNPs improved reprogramming efficiency by more than 7-fold after introduction of four Yamanaka factors. Importantly, ADH-AuNPs generated iPSCs displayed high stemness and pluripotency in vitro and in vivo. Therefore, we provide a cooperative strategy for promoting the iPSC generation efficacy.